PREVENTIVE ACTIVITY AS A FACTOR DEVIANT PREVENTION BEHAVIOR OF ADOLESCENTS (Pedagogy of Higher and Secondary Education, 2006)
In clause is considered questions prévention of activity as factor of the prévention déviation of behaviour of the teenagers, and also basis ofpreventive maintenance déviation of behaviour.